Contractile Force of Transplanted Cardiomyocytes Actively Supports Heart Function After Injury. Issue 15 (8th September 2022) - Stüdemann, Tim; Rössinger, Judith; Manthey, Christoph; Geertz, Birgit; Srikantharajah, Rajiven; von Bibra, Constantin; Shibamiya, Aya; Köhne, Maria; Wiehler, Antonius; Wiegert, J. Simon; Eschenhagen, Thomas; Weinberger, Florian
Abstract : Background: Transplantation of pluripotent stem cell–derived cardiomyocytes represents a promising therapeutic strategy for cardiac regeneration, and the first clinical studies in patients with heart failure have commenced. Yet, little is known about the mechanism of action underlying graft-induced benefits. Here, we explored whether transplanted cardiomyocytes actively contribute to heart function. Methods: We injected cardiomyocytes with an optogenetic off-on switch in a guinea pig cardiac injury model. Results: Light-induced inhibition of engrafted cardiomyocyte contractility resulted in a rapid decrease of left ventricular function in ≈50% (7/13) animals that was fully reversible with the offset of photostimulation. Conclusions: Our optogenetic approach demonstrates that transplanted cardiomyocytes can actively participate in heart function, supporting the hypothesis that the delivery of new force-generating myocardium can serve as a regenerative therapeutic strategy.